Postoperative Pulmonary Hemodynamics and Systemic Inflammatory Response in Pediatric Patients Undergoing Surgery for Congenital Heart Defects - Souza, Maria Francilene S.; Penha, Juliano G.; Maeda, Nair Y.; Galas, Filomena R. B. G.; Abud, Kelly C. O.; Carvalho, Eloisa S.; Thomaz, Ana Maria; Castro, Claudia R. P.; Pereira, Juliana; Lopes, Antonio Augusto (Mediators of Inflammation, 2022)
There is scarce information about the relationships between postoperative pulmonary hemodynamics, inflammation, and outcomes in pediatric patients with congenital cardiac communications undergoing surgery. We prospectively studied 40 patients aged 11 (8–17) months (median with interquartile range) with a preoperative mean pulmonary arterial pressure of 48 (34–54) mmHg who were considered to be at risk for postoperative pulmonary hypertension. The immediate postoperative pulmonary/systemic mean arterial pressure ratio (PAP/SAPIPO, mean of first 4 values obtained in the intensive care unit, readings at 2-hour intervals) was correlated directly with PAP/SAP registered in the surgical room just after cardiopulmonary bypass (r=0.68, p<0.001). For the entire cohort, circulating levels of 15 inflammatory markers changed after surgery. Compared with patients with PAP/SAPIPO≤0.40 (n=22), those above this level (n=18) had increased pre- and postoperative serum levels of granulocyte colony-stimulating factor (p=0.040), interleukin-1 receptor antagonist (p=0.020), interleukin-6 (p=0.003), and interleukin-21 (p=0.047) (panel for 36 human cytokines) and increased mean platelet volume (p=0.018). Using logistic regression analysis, a PAP/SAPIPO>0.40 and a heightened immediate postoperative serum level of macrophage migration inhibitory factor (quartile analysis) were shown to be predictive of significant postoperative cardiopulmonary events (respective hazard ratios with 95% CIs, 5.07 (1.10–23.45), and 3.29 (1.38–7.88)). Thus, the early postoperative behavior of the pulmonary circulation and systemic inflammatory response are closely related and can be used to predict outcomes in this population.